Early delivery of equitable and healthy transport options in new suburbs: Policy, place and people. (September 2020) - Gunn, Lucy; Kroen, Annette; De Gruyter, Chris; Higgs, Carl; Saghapour, Tayebeh; Davern, Melanie
Abstract: Introduction: Planning policies support the development of healthy, liveable cities. Yet, recent research suggests they may not offer enough detail to provide on-the-ground delivery of social and transport infrastructure that supports and impacts healthy, active behaviours and the subjective wellbeing of residents in new developments and growth areas. Methods: Three analyses were conducted. First, planning policies were reviewed using a content analysis to identify environmental features known to support healthy and active behaviours. Then, for two growth area estates located in Melbourne, Australia (Allura and Selandra Rise), the on-the-ground delivery of these planning policies were evaluated using spatial data of key destinations (e.g., shops, schools, and transport) and geographic information systems analysis. Finally, the health and subjective wellbeing of adult residents from these two estates combined ( n  = 352) was assessed using survey methodology. This included asking residents about the importance and satisfaction with access to transport and key destinations. Results: We found that many built environment features were mentioned in the policy documents; however policy standards for dwelling density remain low at 15 dph and distances for accessing activity centres too long at 1 km to adequately support the walkability of new growth areas. We found generally, that average distances to key destinations were longer and more variable in growth areas in comparison to inner city areas and Greater Melbourne overall. For residents, satisfaction with access to destinations differed between the two case study areas. Residents in Allura, where destination and transport access was generally poorer were less satisfied, whilst those in the more walkable and established Selandra Rise area were more satisfied. Conclusions: Although planning policies support the development of active transport and healthy, liveable cities they are insufficient for influencing healthy behaviours when not well implemented. Early delivery of social and transport infrastructure and services must occur early in the development cycle of new growth areas to support healthier and more sustainable behaviours. Highlights: Planning policies were reviewed and measured for their impact on resident health and wellbeing. Residents rated proximity to roads, schools and transport as being important. Residents in more liveable and established growth areas are more satisfied with their area. Planning for liveable growth areas may not be enough for influencing healthy behaviours. Implementation of social and transport services in growth areas must occur early to support health.